Host-mimicking conditions promote Pseudomonas aeruginosa PA14 virulence gene expression - Grace, Amber; Sahu, Rajnish; Owen, Donald R.; Dennis, Vida A. (Frontiers in Microbiology, 2025)
BackgroundPseudomonas aeruginosa is a ubiquitous, opportunistic bacterium whose highly plastic genome and adaptable phenotype have yielded serious treatment challenges for immunocompromised patients. Antibiotic alternatives, such as anti-virulence therapeutics, have gained interest because they disable bacterial virulence mechanisms, thereby restoring the killing efficacy of host immunity or traditional antibiotics. Identifying successful anti-virulence therapeutics may require a paradigm shift from the decades-old antimicrobial susceptibility testing (AST) in Mueller Hinton broth to media that foster optimal virulence expression.MethodsThis study evaluates the virulence gene expression and activity of P. aeruginosa PA14 in host-mimicking conditions, represented by Dulbecco’s Modified Eagle’s Medium (DMEM) without serum, with fetal bovine serum (FBS), or with human serum (HuS) in comparison to standard antimicrobial susceptibility testing conditions, represented by Cation-adjusted Mueller Hinton broth (CAMHB). PA14 twitching motility and pyoverdine production were evaluated under these conditions.ResultsFor the first time, our study reveals that culturing the highly virulent P. aeruginosa PA14 in host-mimicking media enhances the expression of multiple virulence therapeutic targets that are critical to host colonization and infection. RNA sequencing showed that multiple Type III Secretion (T3SS), Type I Secretion (T1SS), pyoverdine biosynthesis, uptake and efflux, and Type IV pili (T4P) initiation genes were promoted when PA14 was transitioned into host-mimicking conditions but remained unchanged when transitioned into standard AST conditions. Moreover, qPCR results disclosed that HuS and FBS delivered differential effects on the expression of membrane-associated virulence genes involved in host colonization. Our macroscopic PA14 twitching motility results aligned more closely with PA14 growth patterns than with virulence gene expression patterns. Our microtiter biofilm assay, however, revealed earlier biofilm formation in DMEM 0 than in AST conditions and both showed inhibited twitching motility in serum conditions. UV-Vis spectra showed that pyoverdine production aligned with our gene expression data, revealing higher pyoverdine production in serum conditions for planktonic PA14.DiscussionOverall, our findings support using host-mimicking conditions to improve the expression of candidate targets for anti-virulence therapeutics against P. aeruginosa PA14 in a planktonic state. These recommendations may be broadly applicable for antivirulence therapeutic screening against multiple bacterial species at large.